Perancangan dan Pembuatan Sistem Informasi Apotek di Puskesmas Banjarsengon - Mahardika Nugraha; Niyatul Muna; Andri Permana Wicaksono; Demiawan Rachmatta Putro Mudiono (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2021)
Banjarsengon public health center is one of the health agencies that deal with patient care and treatment. The pharmacy section of the Banjarsengon Health Center in carrying out registration, recording medical records, drug data collection and managing reports is still done manually. In addition, data collection errors are often encountered which can lead to inaccurate reporting data. The purpose of this research is to solve problems in drug data collection by designing a pharmacy information system at the Banjarsengon health center. The making of pharmacy information system application was using Microsoft Visual Studio 2019. System development was using waterfall method. Data collections consist of observation, interviews and documentation. The result of black box testing showed that this pharmacy information system can operate properly. The advantages are the pharmacy information system been integrated with the operation of pharmacists and management that can reduce the possibility of errors that affect the service to patients, improve the efficiency of the drug recording system quickly and accurately, facilitate pharmacists in recording, reduce and add drug stock automatically and also print reports in pdf form.